Sea vegetables for brine-based inland cultivation - Denisova, Valeriya; Schreiner, Monika; Baldermann, Susanne; Fricke, Anna (Frontiers in Marine Science, 2025)
Rich in nutritional proteins and health-promoting compounds, edible macroalgae, known as “sea vegetables,” provide a valuable and needed alternative food source for a growing human population. Controlled environmental cultivation is a promising approach to provide freshly harvested macroalgal biomass in inland areas. In this context, natural saline groundwater (brine) offers an innovative solution for land-based, urban indoor cultivation of marine organisms. Here, we investigated the suitability of regional brine from the Brandenburg area (Central Europe) for the indoor cultivation of the three different macroalgae: Ulva compressa (“flat gut weed”), Ulva fenestrata (“sea salad”), and Cladophora sp. (Chlorophyta). For the evaluation of brine as cultivation media, we investigated biomass growth (e.g., specific growth rate, SGR) and pigment composition (carotenoids, chlorophylls) at different life stages (e.g., germlings and reproductive thalli). Responses toward the brine media varied between species. Ulva compressa showed comparable growth and elevated chlorophylls when cultivated in brine media, whereas Ulva fenestrata was negatively affected by the brine-based media and stagnated in its reproduction and growth. Also, Cladophora sp. was initially hampered by the brine media but showed a positive shift in growth after 45 days of exposure. For all taxa, high levels of chlorophylls and some of the carotenoids were measured in brine media compared to control media. Assuming that this reflects a stress response during acclimatization to a new cultivation environment, the study provides a promising strategy for macroalgal cultivation in saline groundwater with enhanced levels of photopigments. Given the rising demand for fresh-harvested algal biomass, we suggest fostering the initiated research to further develop “sea vegetable” production in inland areas.